Tourists satisfaction in destination selection determinants and revisit intentions; perspectives from Ghana - Stephen Mahama Braimah; Emmanuel Nii-Ayi Solomon; Robert Ebo Hinson (Cogent Social Sciences)
This paper aimed to investigate destination selection determinants and revisit intentions of international leisure tourists to southern Ghana. It tested the direct paths between destination selection determinants and revisit intention, and investigated the moderating role of satisfaction in the link between the destination selection determinants and revisit intentions. The paper used a structured questionnaire to gather data from 284 respondents. Tourist sites were purposively selected for the survey to collect data from international leisure tourists. The study’s results revealed a significant and positive relationship between destination selection determinants and revisit intentions. However, the dissection of the destination selection determinants’ constructs into individual components revealed that education/learning and ego enhancement are significant predictors of tourist revisit intentions. Overall, the study contributes to the tourism literature by demonstrating how the destination selection determinants are strengthened by the moderating effect of satisfaction. The study’s implications are pertinent as it reinforces the importance of destination marketing and economic variables as determinants of destination choice. Theoretical contributions arise for scholars, and practical implications are presented for service providers and stakeholders within the tourism sector, particularly, those in southern Ghana.